THE ANTAGONIST’S BAD CONDUCT DEPICTED IN WILLIAM SHAKESPEARE’S HAMLET - Sri Widayati; Atika Nur Alami Harahap; Eka Yanualifa Telomensi Sitepu (Universitas Islam Sumatera Utara (UISU), 2019)
This research focused on the antagonist’s bad conduct of the play Hamlet written by William Shakespeare. The main analysis consists of several points. They were betrayal, greediness, and murder. It analyzed how the antagonist tries to satisfy what he wants. This research intends to highlight the people’s way of thinking in considering the way that they use to fulfill their desire. To fulfill their desire, they should use the good ways and consider the negative impact that will be happen for themselves and their surrounding people. They should be able to control their copious desire otherwise they can be a greedy man. On the contrary the antagonist as the character that is discussed in this research has used the bad ways and did not think about the negative impact that will happen. So that, this antagonist’s bad conduct has brought the great disaster for himself and his surrounding people. Finally, through this analysis, the researchers hope that this research will be useful for the readers in considering the way that they use to get their desire.